2017
DOI: 10.1093/bioinformatics/btx252
|View full text |Cite
|
Sign up to set email alerts
|

Predicting multicellular function through multi-layer tissue networks

Abstract: MotivationUnderstanding functions of proteins in specific human tissues is essential for insights into disease diagnostics and therapeutics, yet prediction of tissue-specific cellular function remains a critical challenge for biomedicine.ResultsHere, we present OhmNet, a hierarchy-aware unsupervised node feature learning approach for multi-layer networks. We build a multi-layer network, where each layer represents molecular interactions in a different human tissue. OhmNet then automatically learns a mapping of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
317
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(317 citation statements)
references
References 52 publications
0
317
0
Order By: Relevance
“…Akin to LP [38,75,76] , node embeddings also offer a convenient route to incorporating multiple networks into SL approaches. While methods such as SL-I and SL-A may require concatenating the original networks or integrating them into a single network before learning, recent work has shown that SL-E-based methods can embed information from multiple molecular/heterogeneous networks and learn gene classifiers in tandem [77][78][79][80][81][82][83][84][85] . However, none of these studies have compared the variety of SL-E methods to learning directly on the adjacency matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Akin to LP [38,75,76] , node embeddings also offer a convenient route to incorporating multiple networks into SL approaches. While methods such as SL-I and SL-A may require concatenating the original networks or integrating them into a single network before learning, recent work has shown that SL-E-based methods can embed information from multiple molecular/heterogeneous networks and learn gene classifiers in tandem [77][78][79][80][81][82][83][84][85] . However, none of these studies have compared the variety of SL-E methods to learning directly on the adjacency matrix.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, multiples sources of omics data encode different layers, representing a biological system as a network of networks. This integrated perspective allows for more predictive performances [17,18,19] and has been shown to better characterize the evolution of complex diseases such as cancer [20], as well as to better understand the response to genetic and metabolic perturbations in complex organisms like E. coli [21].…”
Section: Multi-omicsmentioning
confidence: 99%
“…A successful and intuitive application of multilayer gene networks is PARADIGM, a system that models the central dogma of biology (DNA–mRNA–protein) with multiple patient‐specific “omics” measurements, and uses probabilistic inference to identify altered protein activities in each patient. Another application regards the rewiring of protein–protein interactions in 107 human tissues by means of a multilevel interactome that was shown to capture tissue‐specific functions of the proteins …”
Section: Heterogeneous Network To Integrate All Of Biologymentioning
confidence: 99%